1998
DOI: 10.1111/j.1600-0781.1998.tb00002.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of personal solar UV exposure of outdoor workers, indoor workers and adolescents at two locations in Southeast Queensland

Abstract: Quantification of human exposure to solar ultraviolet (UV) radiation at two locations was performed to study the effect of occupation (outdoor workers, schoolchildren and home workers) and location on personal UV exposure. The study took place on 13 and 14 February 1997 in Toowoomba (27.5 degrees S, 151.9 degrees E) and Brisbane (27.4 degrees S, 153.1 degrees E) in Southeast Queensland, Australia. From the data collected by calibrated ambient UV monitoring stations located in Toowoomba and Brisbane, Toowoomba … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
75
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(78 citation statements)
references
References 14 publications
3
75
0
Order By: Relevance
“…These are in excess of occupational exposure limits for UV exposure [19]. The erythemal UV exposures to different population groups have been previously measured at this location by other researchers [3]. The median of the daily erythemal UV exposures to the shoulder for outdoor workers, school children and home workers during normal daily activities were 3.0, 1.5 and 1.2 MED.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…These are in excess of occupational exposure limits for UV exposure [19]. The erythemal UV exposures to different population groups have been previously measured at this location by other researchers [3]. The median of the daily erythemal UV exposures to the shoulder for outdoor workers, school children and home workers during normal daily activities were 3.0, 1.5 and 1.2 MED.…”
Section: Discussionmentioning
confidence: 97%
“…The solar UV exposures to selected human anatomical sites, for example the wrist and shoulder during normal daily activities has been measured using personal UV dosimeters [1][2][3][4][5]. Additionally, previous researchers have employed polysulphone dosimeters to determine the distribution of solar erythemal UV exposure to the human body in predominantly upright positions (for example, [4,6]).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies were found that addressed outdoor workers in Australia (Dobbinson and Knight, 2001;Parisi et al, 1999;Kimlin et al, 1998;Airey et al, 1997;Green et al, 1996;Wong et al, 1996;Girgis et al, 1994;Borland et al, 1991). These studies were carried out mostly in Queensland, with two in Victoria and another in NSW.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Outdoor workers who participated included farmers, Telecom lines staff, and tradespersons. The focus of five of these studies was exposure to UVR (Parisi et al, 1999;Kimlin et al, 1998;Airey et al, 1997;Green et al 1996;Wong et al, 1996) with the remaining studies focusing on the effects of an interventions on outdoor workers' sun protective behaviour (Girgis et al, 1994;Borland et al, 1991) and organisational change (Dobbinson and Knight, 2001). No study was found that had surveyed outdoor workers in NSW to assess their knowledge and sun protective behaviour associated with their risk of skin cancer.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Measurement surveys of the personal exposures have been performed with polysulphone dosimeters [6][7][8][9] and CR-39 dosimeters [10]. These dosimeters were calibrated to measure personal erythemal exposures resulting predominantly from the UVB (280-320 nm) waveband.…”
Section: Introductionmentioning
confidence: 99%